The Influence Of Religiosity And Reference Groups On Purchasing Decisions - Sarah, Sarah Fitria; Artanti, Yessy (BISNIS, 2020)
In recent years the growing fashion trend in Indonesia is a muslim fashion trend. The current trend of muslim clothing in Indonesia such as Rabbani muslim clothing that is in accordance with the teachings of Islamic religion is polite, closed and designed with materials that are not thin or dreamy. This study aims to analyze and discuss the effect of Religiosity and Reference Groups on Purchasing Decisions. This study uses a nonprobability sampling method with judgmental sampling method. The number of samples in this study were 220 respondents where selected were respondents who had bought  Muslim clothing Rabbani and aged 17-60 years. The measurement scale uses a likert scale. Data analysis uses multiple linear regression analysis tools. Distribution questionnaires are done offline. The results of this study indicate that Religiosity does not significantly influence Purchasing Decisions. The results also showed that the Reference Group had a significant effect on Purchasing Decisions. Keywords : religiosity, reference groups, and purchasing decisions